Bone mineral density and microstructure of the elbow in baseball pitchers: An analysis by second-generation HR-pQCT - Sada, K.; Chiba, K.; Kajiyama, S.; Okazaki, N.; Tomita, M.; Osaki, M. (Journal of Clinical Densitometry, 2020)
Background: Baseball pitchers` elbows are exposed to repeated overloading during the throwing motion, which causes bone structural changes such as bone sclerosis and osteophyte formation. They have been observed by clinical CT and MRI, while the bone microstructural change has not yet been studied in vivo. The aims of this study were to establish a method of imaging the elbow joint using second-generation high-resolution peripheral quantitative CT and to investigate the bone microstructural change in baseball pitchers` dominant elbows. Methods: The subjects were 17 baseball pitchers. The elbow was fixed using a custom-made cast and scanned by second-generation high-resolution peripheral quantitative CT. The scan conditions were as follows: voxel size 60.7 µm, integration time 43 ms, scan length 30.6 mm, and total scan time 8 min. Volumetric bone mineral density (vBMD) and trabecular bone microstructure were analyzed in the 6.5-mm3 cubic regions set in the capitellum and trochlea, and the dominant and nondominant elbows were compared. Results: vBMD, bone volume fraction (BV/TV), and trabecular thickness (Tb.Th) at the capitellum were significantly higher in the dominant elbow than in the nondominant elbow. On the other hand, no parameters at the trochlea were significantly different. Conclusions: Higher vBMD accompanied by thicker trabecular bone was observed at the capitellum. These bone microstructural changes would reflect the valgus stress generated by the pitching motion in the elbow joint.